2023
DOI: 10.2196/41388
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Dissemination of COVID-19–Related Articles Across Social Media: Altmetrics Study

Abstract: Background The use of social media assists in the distribution of information about COVID-19 to the general public and health professionals. Alternative-level metrics (ie, Altmetrics) is an alternative method to traditional bibliometrics that assess the extent of dissemination of a scientific article on social media platforms. Objective Our study objective was to characterize and compare traditional bibliometrics (citation count) with newer metrics (Alt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Previous studies have analyzed the attributes of the top COVID-19 articles [ 15 , 16 ], but none have directly compared the AAS scores of COVID-19–related versus non–COVID-19–related articles. We found that despite consisting of only 4% (27/747) of the manuscripts published, the average AAS for COVID-19–related articles was nearly 10-fold higher than non–COVID-19–related articles, which was significant by multivariable analysis ( P <.001).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have analyzed the attributes of the top COVID-19 articles [ 15 , 16 ], but none have directly compared the AAS scores of COVID-19–related versus non–COVID-19–related articles. We found that despite consisting of only 4% (27/747) of the manuscripts published, the average AAS for COVID-19–related articles was nearly 10-fold higher than non–COVID-19–related articles, which was significant by multivariable analysis ( P <.001).…”
Section: Discussionmentioning
confidence: 99%
“…(https://www.altmetric.com/about-us/our-data/our-sources/) Altmetric attention scores have been found to be associated with citation counts 7,9 and journal impact factor 10 and those articles with higher Altmetric scores (i.e., those promoted online simultaneously) were more likely to be cited in public policy documents 11 . This attention score has also been shown to be significantly higher for Covid-19 related articles than for non-Covid-19 articles in 2020 12 .…”
Section: Introductionmentioning
confidence: 99%